Development and Validation of the Vark Instrument in Citizenship Education Learning: A Structural Equation Modeling Approach for More Accurate Learning Style Measurement - Delfiyan Widiyanto; Novitasari Novitasari; Mashud Syahroni; Alifia Revan Prananda; Tholibah Mujtahidah; Annisa Istiqomah (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This research aims to develop and test the VARK learning style instrument in Citizenship Education Learning using SEM (Structural Equation Modeling) to produce a valid, reliable and goodness of fit instrument for more accurate measurement of learning styles. Methodology: This study employs quantitative methods to evaluate the VARK learning styles theory in citizenship education through three primary phases: (1) assessing interrater validity to verify the construct's feasibility, (2) establishing empirical validity via Confirmatory Factor Analysis (CFA) to examine the construct's effectiveness and reliability, and (3) utilizing Structural Equation Modeling (SEM) along with goodness-of-fit (GOF) analysis to determine the model's overall suitability. Main Findings: The findings of this research indicate that the VARK learning styles framework and related instruments in citizenship education are very suitable for measurement. The model meets the main criteria: (1) Inter-rater Validity Test confirms its validity, (2) Construct Validity Test using Confirmatory Factor Analysis shows validity and reliability, and (3) Goodness-of-Fit Test places the model in the acceptable fit category. So this instrument can be used to measure learning styles accurately. Novelty/Originality of this study: The novelty of this research lies in the development and instrument of VARK learning styles in Citizenship Education learning which was tested using Structural Equation Modeling (SEM) to produce a feasible and accurate instrument for measuring learning styles.